A Taste of Honey: Early Medieval Chinese Writings about Sweeteners. (1st January 2020) - Milburn, Olivia
Abstract : This paper focuses on the small group of writings from the Wei-Jin period about different kinds of sweeteners used in food and drink. Apart from any question of literary merit in these writings, there is the issue of status: all sugars were expensive, and some were extremely rare, and to consume such a sugar was a potent sign of privilege. It is not surprising that all early medieval poems and prose about sweeteners focus on the sugars considered to be most prestigious: honey, manna, and sugarcane. These writings influenced later works on the same subject, and provide the earliest surviving descriptions of the importance of sugars in Chinese culture.